A swedish diplomat and his reporting on the Holocaust - Apelblat, Mose. (2015)
Zakres i treść: Jan Karski and his reporting, historians on von Otter, von Otter's testimonies, reporting in August 1942.
Tyt. nagł.
Streszcz. pol.